2016
DOI: 10.3389/fpls.2016.00625
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cryptic, Systemic Botrytis Infections in Symptomless Hosts

Abstract: Botrytis species are generally considered to be aggressive, necrotrophic plant pathogens. By contrast to this general perception, however, Botrytis species could frequently be isolated from the interior of multiple tissues in apparently healthy hosts of many species. Infection frequencies reached 50% of samples or more, but were commonly less, and cryptic infections were rare or absent in some plant species. Prevalence varied substantially from year to year and from tissue to tissue, but some host species rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 42 publications
2
69
0
Order By: Relevance
“…Recently, several Botrytis species were shown to exhibit endophytic stages in their lifecycles in a range of flowering plants (Barnes & Shaw, ; Sowley et al ., ; Grant‐Downton et al ., ; Shaw et al ., ). Shaw et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several Botrytis species were shown to exhibit endophytic stages in their lifecycles in a range of flowering plants (Barnes & Shaw, ; Sowley et al ., ; Grant‐Downton et al ., ; Shaw et al ., ). Shaw et al .…”
Section: Discussionmentioning
confidence: 99%
“…Shaw et al . () found B. cinerea , B. pseudocinerea , B. mali isolates and an undescribed Botrytis sp. existing as cryptic infections in dandelion.…”
Section: Discussionmentioning
confidence: 99%
“…In general, B. cinerea is considered to be a necrotroph, which draws nourishment from dead host tissue and produces initially local (‘primary’) necrotic lesions, which subsequently expand to actively cause plant tissue decomposition (Horst, ; Jarvis, ; Coertze & Holz, ; Elad et al ., ). In contrast, recent studies have revealed that B. cinerea can also cause symptomless systemic infection in several host plants including Primula spp., lettuce ( Lactuca sativa ), Arabidopsis thaliana and Taraxacum vulgare (Barnes & Shaw, ; Rajaguru & Shaw, ; Sowley et al ., ; Shaw et al ., ). In this type of infection the fungus grows along with the plant and enters newly expanding organs, without producing symptoms, until the plant becomes physiologically susceptible, typically at flowering.…”
Section: Introductionmentioning
confidence: 97%
“…The latter can lead to secondary siRNA biogenesis through RNA-dependent RNA polymerase (RDR) activity to form double-stranded RNA (dsRNA), which is then sophisticated RNA-based manipulation was surprising as B. cinerea depends on inducing cell death for a successful necrotrophic lifestyle [45], hence such downregulation of host defence transcripts might seem superfluous. However, B. cinerea and other species in the genus can evade cell death induction and host defences, and grow as asymptomatic endophytes [46,47]. It is tempting to speculate that in such interactions, B. cinerea sRNAs might suppress host cell death responses, while plant sRNAs in turn might suppress fungal virulence mechanisms, thereby modulating the pathogenic (necrotic) interaction into an (asymptomatic) symbiosis.…”
Section: Mobile Small Rnas -Key Agents In 'Information Warfare'?mentioning
confidence: 99%